Noise and Fluctuations in Nanowire Biosensors★. Issue 1 (2015) - Tulzer, Gerhard; Heitzinger, Clemens
Abstract: This work deals with the stochastic simulation of a nanowire biosensor surface and the surrounding liquid domain for DNA detection. The objective is an analysis of the fluctuations and of the biological noise induced by the inherent randomness of the hybridization process at the surface. We consider a coupled system of diffusion-reaction equations to model the movement of DNA oligomers as well as the hybridization processes at the functionalized surface of the sensor. Since analytical solutions cannot be derived, numerical investigation is necessary. Here, we present an algorithm different from the already published one in Tulzer and Heitzinger (2014) and show the non-monotonic behaviour of the variance in certain regimes. The variance determines the detection limit, which is an important quantity for optimal sensor design.